Effects of shot peening on microstructure, thermal performance, and failure mechanism of thermal barrier coatings. Issue 6 (18th February 2022) - Liu, Guanxi; Shen, Zaoyu; Huang, Guanghong; He, Limin; Mu, Rende; Zhao, Wenjun
Abstract: Shot peening might be a potential technology to optimize the interface microstructure, plays a critical role on failure behaviors, of thermal barrier coatings (TBCs). It remains a significant challenge to understand the influence of shot peening on microstructure, oxidation resistance, and thermal shock life. In this work, the Y2 O3 ‐stabilized ZrO2 TBCs have been deposited by EB‐PVD. The phase, microstructure, thermal performance, and failure mechanism of TBCs have been systemically investigated after shot peening. The shot peening process can improve the planeness of interface and reduce the formation of the cauliflower‐liked microstructure in TBCs. After shot peening, the TBC coatings exhibit relatively good isothermal oxidation resistance and high thermal shock life due to the optimization of TGO growth and the thermal stability. The phase transformation, TGO growth, and cracks extension might give rise to the failure of TBCs. This work might guide the investigation of the improvement of interface microstructure and failure behaviors.